Causes of Motor Vehicle Traffic Violations by Minors and Prevention Strategies (Case Study at Semarang POLRES SATLANTAS 2023) - Rigma Vellanika Shamsahara*; Nani Mediatati; Agus Bambang Nugraha (Riwayat: Educational Journal of History and Humanities, 2023)
This research aims to determine the factors causing motor vehicle traffic violations by minors, as well as the strategies carried out by the Semarang POLRES SATLANTAS to overcome them. The research respondents were BAUR, Semarang POLRES SATLANTAS ticket, Semarang POLRES SATLANTAS CAMSEL KANIT, Semarang POLRES SATLANTAS ticket BAMIN, as well as ten minors who violated traffic regulations. Data collection techniques used observation, interviews, documentation studies, literature studies, and qualitative analysis. The research results show that the causes of traffic violations by minors include human, vehicle, road and environmental factors. The strategy for dealing with traffic violations carried out by the Semarang POLRES SATLANTAS is through efforts (1). Pre-emptive, namely carrying out socialization of good and correct traffic in schools and industry through lectures and counseling, (2). Preventive means installing ETLE (Electronic Traffic Law Enforcement) on every traffic sign or vehicle driven by the police to eliminate the opportunity to commit traffic violations, (3). Repressive, namely carrying out law enforcement, if the police find that a minor does not have a driver's license driving a motorized vehicle, the police will issue a ticket, detain the motor vehicle, and summon the parents. Even though these three strategies have been implemented, they have not been completely successful in reducing the number of traffic violations by minors in Semarang Regency.